2019
DOI: 10.1371/journal.pone.0218760
|View full text |Cite
|
Sign up to set email alerts
|

Feature selection and transformation by machine learning reduce variable numbers and improve prediction for heart failure readmission or death

Abstract: Background The prediction of readmission or death after a hospital discharge for heart failure (HF) remains a major challenge. Modern healthcare systems, electronic health records, and machine learning (ML) techniques allow us to mine data to select the most significant variables (allowing for reduction in the number of variables) without compromising the performance of models used for prediction of readmission and death. Moreover, ML methods based on transformation of variables may potentially fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 25 publications
3
40
0
2
Order By: Relevance
“…of patients Setting Data source No. of features Primary outcome assessed Adler, E.D (2019) [10] 2006–2017 5 822 Inpatient and outpatient EHR and Trial 8 All-cause mortality Ahmad, T (2018) [30] 2000–2012 44 886 Inpatient and outpatient Registry 8 1-year all-cause mortality Allam, A (2019) [31] 2013 272 778 Inpatient Claims dataset 50 30-day all-cause readmission Angraal, S (2020) [13] 2006–2013 1 767 Inpatient Trial 26 All-cause mortality and HF hospitalization Ashfaq, A (2019) [32] 2012–2016 7 655 Inpatient and outpatient EHR 30-day all-cause readmission Awan, SE (2019) [33] 2003–2008 10 757 Inpatient and outpatient EHR 47 30-day HF-related readmission and mortality Chen, R (2019) [34] 2014–2017 98 Inpatient Prospective Clinical and MRI 32 Cardiac death, heart transplantation and HF-related hospitalization Chicco, D (2020) [11] 2015 299 Inpatient Medical records 13 One year survival Chirinos, J (2020) [35] 2006–2012 379 Inpatient Trial 48 Risk of all-cause death or heart failure-related hospital admission Desai, R.J (2020) [6] ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of patients Setting Data source No. of features Primary outcome assessed Adler, E.D (2019) [10] 2006–2017 5 822 Inpatient and outpatient EHR and Trial 8 All-cause mortality Ahmad, T (2018) [30] 2000–2012 44 886 Inpatient and outpatient Registry 8 1-year all-cause mortality Allam, A (2019) [31] 2013 272 778 Inpatient Claims dataset 50 30-day all-cause readmission Angraal, S (2020) [13] 2006–2013 1 767 Inpatient Trial 26 All-cause mortality and HF hospitalization Ashfaq, A (2019) [32] 2012–2016 7 655 Inpatient and outpatient EHR 30-day all-cause readmission Awan, SE (2019) [33] 2003–2008 10 757 Inpatient and outpatient EHR 47 30-day HF-related readmission and mortality Chen, R (2019) [34] 2014–2017 98 Inpatient Prospective Clinical and MRI 32 Cardiac death, heart transplantation and HF-related hospitalization Chicco, D (2020) [11] 2015 299 Inpatient Medical records 13 One year survival Chirinos, J (2020) [35] 2006–2012 379 Inpatient Trial 48 Risk of all-cause death or heart failure-related hospital admission Desai, R.J (2020) [6] ...…”
Section: Resultsmentioning
confidence: 99%
“… First Author (year) Study Region No. of patients % Black Age % male % Hypertension % IHD Adler, E.D (2019) [10] USA and Europe 5 822 60.3 Ahmad, T (2018) [30] Europe 44 886 73.2 63 Allam, A (2019) [31] USA and Europe 272 778 73 ± 14 51 Angraal, S (2020) [13] USA, Canada, Brazil, Argentina, Russia, Georgia 1 767 72 (64–79) 50 Ashfaq, A (2019) [32] Europe 7 655 78.8 57 Awan, SE (2019) [33] Australia 10 757 82 ± 7.6 49 67 55 Chen, R (2019) [34] China 98 47 ± 14 79 23 Chicco, D (2020) [34] Pakistan 299 40–95* 65 Chirinos, J (2020) [35] USA, Canada, Russia 379 7.4 70 (62–77) 53.5 94.5 30.6 Desai, R.J (2020) [6] USA 9 502 5.1 78 ± 8 45 87.1 22 F...…”
Section: Resultsmentioning
confidence: 99%
“…Even with the emergence of the ML algorithm, 29 out of 36 articles adopted traditional statistical methods. Among these studies, ~ 90% used LR either as a baseline [ 56 , 58 , 60 , 62 64 , 68 , 73 , 74 , 76 78 , 83 , 85 87 ] or the main model in prediction [ 60 , 69 , 71 , 82 , 88 90 ], and 3 studies derived their own risk scores on the basis of LR variable coefficients [ 61 , 66 , 84 ]. In the remaining 3 papers, the prognosis of readmission was carried out with Cox regression survival analysis.…”
Section: Application To Readmissionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] Although many studies have concluded that AI-based models are superior to traditional models for risk stratification, other studies have observed otherwise. 14,[27][28][29][30][31][32][33][34][35][36][37][38][39] While clinical factors have primarily been used to predict readmission, there has also been interest in incorporating sociodemographic factors into models to more accurately account for patients' sociopersonal contexts, which are increasingly recognized to affect health-related outcomes. [10][11][12][13]40 This is critical because health behaviors, social factors, and economic factors are estimated to account for 70% of a person's health.…”
Section: Predictive Analytics For Hospital Readmissionmentioning
confidence: 99%